The Effect of Brand Awareness on Purchase Decisions Moderated by Product Quality and the Role of Experience as Mediation - Pratiwi, Yulia Citra; Ramanda, Eva Ayu; Aprilliyani, Aprilliyani; Agustina, Khaila Devana (Lentera Ilmu Nusantara, 2024)
There are various trademarks of shampoo products in Indonesia, but it turns out that several new brands have been able to occupy the Top Brand Index position in the last 5 years, this shows that there is quite competitive competition in the industry. The Pantene brand, which has been present for a long time, turns out to occupy the second position in the data. Digitalization has changed consumer patterns in this era, social media and the internet have changed consumer patterns in making purchases and also marketing patterns carried out. Brand awareness and product quality are examples of aspects of consumer consideration in making purchase decisions. The research was conducted to analyze this with the boundaries of Bekasi regency and used 100 respondents as a sample. Data was collected using a questionnaire with a purposive sampling technique and analyzed with the help of Smart Partial Least Square software. The results of the study show that brand awareness and product quality have a significant role in helping to increase consumer purchase decisions in the future.